Mechanisms of internal curing water release from retentive and non-retentive superabsorbent polymers in cement paste. (September 2021) - Zhong, Peihua; Hu, Zhangli; Griffa, Michele; Wyrzykowski, Mateusz; Liu, Jiaping; Lura, Pietro
Abstract: This paper examines the mechanisms of desorption within cement pastes for superabsorbent polymers (SAP) with different sorption kinetics: retentive and non-retentive (self-releasing). Despite the different behavior in solution, both SAP types mitigated the autogenous shrinkage of cement pastes. 1 H NMR and X-ray tomography showed that the cavities formed by both SAP types were saturated until 9–11 h after mixing, while the entrained water in the cavities redistributed to the cement matrix afterwards. In particular, the non-retentive SAP might have rapidly released the absorbed water, but the released water stayed in the original cavities. Therefore, the behavior of the SAP in the pore solution may not completely determine their internal curing performance in cement pastes. In particular, the initial absorption that forms the solution-filled cavities might be more important than whether the SAP are able to retain the solution for extended periods of time or not.